I am trying to prove theorem 9.2 from book "Lectures on Linear Partial Differential Equations" wtitten by G. Eskin. In proof of this theorem is inequality which makes problems for me. Firstly I remind designation.

Multi-index: $\alpha=(\alpha_{1}, \ldots , \alpha_{n}) \in \mathbb{Z}_{+}^{n}$, length of multi-index: $| \alpha | = \sum_{i=1}^{n} \alpha_{i}$, partial differential operator: $$D^{\alpha} = \frac{\partial ^{|\alpha|}}{\partial x_{1}^{\alpha_{1}} \ldots \partial x_{n}^{\alpha_{n}}}.$$ Moreover $|x|=\sqrt{x_1^2+ \ldots + x_n^2}$, Schwartz space: $$\mathcal{S}(\mathbb{R}^n) = \{f \in C^{\infty}(\mathbb{R}^n) \colon \sup_{x \in \mathbb{R}^{n}} (1+|x|)^{m}|D^{\beta}f(x)| < \infty, \: m \in \mathbb{N}, \: \beta \in \mathbb{Z}_{+}^{n} \}.$$ Seminorm in Schwartz space: $$ \|f\|_{m,\mathcal{S}} = \sup_{x \in \mathbb{R}^{n}} (1+|x|)^{m} \sum_{|\beta| = 0}^{m} |D^{\beta}f(x)|. $$ For every function $f \in \mathcal{S}(\mathbb{R}^n)$, for every multi-index $\beta \in \mathbb{Z}_{+}^{n}$ and for every $m \in \mathbb{N}$ we have \begin{equation*} (1+|x|)^{m}D^{\beta}f(x) = \int \limits_{-\infty}^{x_1} \cdots \int \limits_{-\infty}^{x_n} D^{(1,\ldots,1)}[(1+|y|)^{m}D^{\beta}f(y)] \; dy_n \ldots dy_1. \end{equation*}

We need to show inequality. \begin{equation} \| f \|_{m,\mathcal{S}} \leq C_{1} \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^m |D^{\beta} f(y)| \; dy, \quad f \in \mathcal{S}(\mathbb{R}^n). \end{equation}

I used above properties, used Liebniz and I've got this:

\begin{eqnarray*} \|f\|_{m,\mathcal{S}} &=& \sup_{x \in \mathbb{R}^{n}} (1+|x|)^{m} \sum_{|\beta| = 0}^{m} |D^{\beta}f(x)| = \sup_{x \in \mathbb{R}^{n}} \sum_{|\beta| = 0}^{m} \left| (1+|x|)^{m} D^{\beta}f(x) \right|\\ &=& \sup_{x \in \mathbb{R}^{n}} \sum_{|\beta| = 0}^{m} \left| \int \limits_{-\infty}^{x_1} \cdots \int \limits_{-\infty}^{x_n} D^{(1,\ldots,1)}[(1+|y|)^{m}D^{\beta}f(y)] \; dy_n \ldots dy_1 \right|\\ &\leq & \sup_{x \in \mathbb{R}^{n}} \sum_{|\beta| = 0}^{m} \int \limits_{-\infty}^{x_1} \cdots \int \limits_{-\infty}^{x_n} \left| D^{(1,\ldots,1)}[(1+|y|)^{m}D^{\beta}f(y)] \right| \; dy_n \ldots dy_1 \\ & \leq & \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \left| D^{(1,\ldots,1)}[(1+|y|)^{m}D^{\beta}f(y)] \right| \; dy = \\ & = & \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \left| \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} D^{\alpha}\left( (1+|y|)^{m} \right) \cdot D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ &=& \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \left| \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} c_0 \cdot y^{\alpha} |y|^{-2|\alpha|} (1+|y|)^{m} \cdot D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ & \leq & \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} \left| c_0 \cdot y^{\alpha} |y|^{-2|\alpha|} (1+|y|)^{m} \cdot D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ & \leq & \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} c_0 \cdot |y|^{|\alpha|} |y|^{-2|\alpha|} (1+|y|)^{m} \cdot \left| D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ &=&\sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} c_0 \cdot |y|^{-|\alpha|} (1+|y|)^{m} \cdot \left| D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ &=&\sum_{|\beta| = 0}^{m}\sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} c_0 \cdot \int _{\mathbb{R}^n} |y|^{-|\alpha|} (1+|y|)^{m} \cdot \left| D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy \\ \end{eqnarray*}

It is almost what I need - problem is with factor $|y|^{-|\alpha|}$. Has someone idea how to prove it? Thanks in advance.

  • $\begingroup$ When you're differentiating $(1+\lvert y\rvert)^m$, you reduce the exponent. But you still have a problem near $0$. Instead of $(1+\lvert y\rvert)^m$, I suggest you use $(1 + \lvert y\rvert^2)^{m/2}$. That's much nicer for differentiating. $\endgroup$ – Daniel Fischer Sep 5 '13 at 21:30
  • $\begingroup$ Yeah, you are right about diferentiation in $0$, but we ignore this. I have to use this factor, because even if we can find constant $c$ such that $$(1+|y|)^m \leq c \cdot (1+|y|^2)^{m/2}$$ then there is no relation between $D^{\alpha}(1+|y|)^m$ and $D^{\alpha}(1+|y|^2)^{m/2}$. We know that $\alpha \in \{0,1\}^n$ so $$D^{\alpha}(1+|y|)^m= c \cdot y^{\alpha} |y|^{-2|\alpha|}\cdot (1+|y|)^m $$. Moreover we know that $$|y^{\alpha}| \leq |y|^{|\alpha|}.$$ I use this in calculation above $\endgroup$ – Marcin Sep 5 '13 at 22:15
  • 1
    $\begingroup$ First, I want to ask why you got $|y|^{-|\alpha|}$? I think it should be $|y|^{-|\alpha|+1}$, then the integral converges at $0$. Also, could you post a copy of Theorem 9.2, so I may see more clearly what's going on? $\endgroup$ – L. Xu Sep 7 '13 at 20:57
  • $\begingroup$ @L.Xu I took a screenshots from google books, you can find them here -> link. How you got $|y|^{1-|\alpha|}$?? $\endgroup$ – Marcin Sep 14 '13 at 19:35
  • $\begingroup$ @L.Xu From Newton formula $$D^{\alpha}\left( (1+|y|)^{m} \right) = \sum _{j=0}^{m} \binom{m}{j}D^{\alpha}\left( |y|^{j} \right).$$ We know that $\alpha \in \{0,1\}^n$, so $$D^{\alpha}\left( |y|^{j} \right) = c_{j} \cdot y^{\alpha} \cdot |y|^{m-2|\alpha|}.$$ We know also $$ |y^{\alpha}| \leq |y|^{|alpha|}$$ so when $c = \max_{j}|c_j|$ then we have $$\left| D^{\alpha}\left( (1+|y|)^{m} \right) \right| \leq c |y|^{-\alpha} (1+|y|)^{m}$$ $\endgroup$ – Marcin Sep 14 '13 at 21:18

First for $j$ is odd, \begin{align} D^\alpha\left(|y|^j\right)=c_j\cdot y^\alpha\cdot |y|^{j-2|\alpha|}. \end{align} For $j$ is even, $D^\alpha\left(|y|^j\right)=0$ if $j<2|\alpha|$. Then let's check \begin{align} \left|D^\alpha\left((1+|y|)^m\right)\right|\le\sum_{j=0}^m \left(\begin{array}{cc}m\\j \end{array}\right)\left|D^\alpha\left(|y|^j\right)\right|=\sum_{j=1}^m c_j\cdot \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|}\le \sum_{j=1}^m c_j\cdot |y|^{j-|\alpha|}. \end{align} In the above sum, the first term vanishes since it's a constant, the rest of them have similar form with the exponent of $|y|$ bigger than or equal to $1-|\alpha|$. Then it's clear that \begin{align} \left|D^\alpha\left((1+|y|)^m\right)\right|\le C|y|^{1-|\alpha|}(1+|y|)^m, \end{align} so the integral (cited from your question) \begin{align} \int _{\mathbb{R}^n} \left|D^\alpha\left((1+|y|)^m\right)\right|\cdot \left| D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy,\quad |\alpha|\le n, \end{align} converges, so the whole integral converges.

In the following I'll answer why \begin{equation} \| f \|_{m,\mathcal{S}} \leq C \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^m |D^{\beta} f(y)| \; dy, \quad f \in \mathcal{S}(\mathbb{R}^n). \end{equation} From the link of the textbook you provided, it seems to me that the author wants to say this is obvious and easy to derive. I considered about it for long, but I'm not able to give any easy way to it (just as you said, the term $|y|^{1-|\alpha|}$ is hard to get rid of). First, as you deduced in the question, we have \begin{align} \| f \|_{m,\mathcal{S}} \le& \sum_{|\beta| = 0}^{m} \int _{\mathbb{R}^n} \left| \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} D^{\alpha}\left( (1+|y|)^{m} \right) \cdot D^{\gamma} \left( D^{\beta}f(y) \right) \right| \; dy. \end{align} Then from the calculating result I give above, we know \begin{align} \| f \|_{m,\mathcal{S}} \le& \sum_{|\beta| = 0}^{m} \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} \int _{\mathbb{R}^n} \left| D^{\alpha}\left( (1+|y|)^{m} \right)\right| \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy \\ \le& \sum_{|\beta| = 0}^{m} \sum _{\alpha + \gamma = (1,\ldots ,1)} \binom{n}{|\gamma|} \sum_{j=1}^m c_j\cdot \int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy. \end{align} Now let's consider to simplify the integral \begin{align} \int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy. \end{align} I'll just show for $\alpha=(1,1,\ldots,1)$ and $j=1$, other cases are similar and easier. In this case, the above integral becomes \begin{align} \int _{\mathbb{R}^n} \left|y_1y_2\ldots y_n\right|\cdot |y|^{1-2n} \cdot \left| D^{\beta}f(y) \right| \; dy. \end{align} Rewrite it as \begin{align} \int _{\mathbb{R}^n} y_1|y|^{1-2n} \cdot F_1(y) \; dy, \end{align} where $F_1(y)=\textrm{sign}(y_1)\left|y_2\ldots y_n\right|\cdot \left| D^{\beta}f(y) \right|$. Note that $F_1$ is non-differentiable only on zero measure set (because $D^{\beta}f(y)$ is smooth), then integrating by part (this integration by part is not easy to prove since the derivative has jumps somewhere) we have \begin{align} \int _{\mathbb{R}^n} \left|y_1y_2\ldots y_n\right|\cdot |y|^{1-2n} \cdot \left| D^{\beta}f(y) \right| \; dy&=\int _{\mathbb{R}^{n-1}} \left(\int _{\mathbb{R}} F_1(y) \cdot |y|^{1-2n}y_1 \; dy_1\right)dy_2\ldots dy_n \\ &=-C\int _{\mathbb{R}^{n-1}} \left(\int _{\mathbb{R}} \frac{\partial F_1}{\partial y_1}(y) \cdot |y|^{3-2n} \; dy_1\right)dy_2\ldots dy_n \\ &\le C\int _{\mathbb{R}^{n}} \left|\frac{\partial F_1}{\partial y_1}(y)\right| \cdot |y|^{3-2n} \; dy \\ &\le C\int _{\mathbb{R}^{n}} \left|y_2\ldots y_n\right|\cdot \left| D_1D^{\beta}f(y) \right| \cdot |y|^{3-2n} \; dy. \end{align} Repeating the above procedure (set $F_2(y)=\textrm{sign}(y_2)\left|y_3\ldots y_n\right|\cdot \left| D_1D^{\beta}f(y) \right|\ldots$ and so on), we can finally get \begin{align} \int _{\mathbb{R}^n} \left|y_1y_2\ldots y_n\right|\cdot |y|^{1-2n} \cdot \left| D^{\beta}f(y) \right| \; dy\le& C\int _{\mathbb{R}^{n}} \left| D^{\alpha}D^{\beta}f(y) \right| \cdot |y| \; dy \\ \le& C\int _{\mathbb{R}^{n}} (1+|y|)^m \cdot \left| D^{\alpha}D^{\beta}f(y) \right| \; dy. \end{align} So we have for all $\alpha+\gamma=(1,1,\ldots,1)$, $|\beta|\le m$, \begin{align} \int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy\le C\int _{\mathbb{R}^{n}} (1+|y|)^m \cdot \left| D^{(1,1,\ldots,1)}D^{\beta}f(y) \right| \; dy. \end{align} Summing up all the above, we can conclude \begin{equation} \| f \|_{m,\mathcal{S}} \leq C \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^m |D^{\beta} f(y)| \; dy, \quad f \in \mathcal{S}(\mathbb{R}^n). \end{equation}

Moreover, I realized that in the textbook by this result the author just wants to show \begin{equation} \| f \|_{m,\mathcal{S}}^2 \leq C \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^{2m+n+1} |D^{\beta} f(y)|^2 \; dy, \quad f \in \mathcal{S}(\mathbb{R}^n). \end{equation} If we show this directly, things can be less complicated. First by C-S inequality and Newton's formula, \begin{align} \left(\int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy\right)^2\le& C\int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} (1+|y|)^{n+1} \cdot \left| D^{\beta+\gamma}f(y) \right|^2 \; dy \\ =& C\sum_{k=0}^{n+1}\left(\begin{array}{cc}n+1\\k \end{array}\right)\int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j+k-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right|^2 \; dy. \end{align} Then we set $$F_1(y)=\textrm{sign}(y_1)\left|y_2\ldots y_n\right|\cdot \left| D^{\beta+\gamma}f(y) \right|^2.$$ In this case, $F_1(y)$ is everywhere smooth with respect to $y_1$ except at $0$, and the integration by part is easy to prove (split the integral by $\int_{-\infty}^{-\epsilon}+\int^{\infty}_{\epsilon}$ and let $\epsilon\to0$ to approximate it) and we have

\begin{align} \int _{\mathbb{R}^n} |y|^{j+k-2|\alpha|}y_1 \cdot F_1(y) \; dy&=-C\int _{\mathbb{R}^{n-1}} \left(\int _{\mathbb{R}} \frac{\partial F_1}{\partial y_1}(y) \cdot |y|^{j+k-2|\alpha|+2} \; dy_1\right)dy_2\ldots dy_n \\ &\le C\int _{\mathbb{R}^{n}} \left|\frac{\partial F_1}{\partial y_1}(y)\right| \cdot |y|^{j+k-2|\alpha|+2} \; dy \\ &\le C\int _{\mathbb{R}^{n}} \left|y_2\ldots y_n\right|\left(\left| D^{\beta+\gamma}f(y) \right|^2+\left| D_1D^{\beta+\gamma}f(y) \right|^2\right) \cdot |y|^{j+k-2|\alpha|+2} \; dy. \end{align} Repeating this procedure we can finally get \begin{align} \left(\int _{\mathbb{R}^n} \left|y^\alpha\right|\cdot |y|^{j-2|\alpha|} \cdot \left| D^{\beta+\gamma}f(y) \right| \; dy\right)^2\le C \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^{m+n+1} |D^{\beta} f(y)|^2 \; dy. \end{align} Therefore \begin{equation} \| f \|_{m,\mathcal{S}}^2 \leq C \sum_{|\beta|=0}^{n+m} \int _{\mathbb{R}^n} (1+|y|)^{m+n+1} |D^{\beta} f(y)|^2 \; dy, \quad f \in \mathcal{S}(\mathbb{R}^n). \end{equation} This is stronger than what we want.

  • $\begingroup$ Thanks for reply. I got it 3 days before you ;) a I used similar explanation. I add only that if $\alpha = 0$ and $j=0$ then $D^{\alpha}(|x|^j)= 1$, but this is not a problem, because integral $\int_{\mathbb{R}^n}|D^{\beta+\gamma}f(y)| \; dy$ is finite as Schwartz space is subset of $L^{p}(\mathbb{R}^n)$ and $p \geq 1$. $\endgroup$ – Marcin Sep 21 '13 at 10:48
  • $\begingroup$ What do you mean by "similar explanation"? You mean you had got all my above argument similarly, or just for the "$|y|^{1-|\alpha|}$" argument? $\endgroup$ – L. Xu Sep 21 '13 at 16:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.